Influence of Patient Demographics and Surgical Characteristics on Pass Rates of Return-to-Activity Tests in Anterior Cruciate Ligament–Reconstructed Patients Before Physician Clearance. Issue 6 (November 2021) - Norte, Grant E.; Goetschius, John W.; Slater, Lindsay V.; Hart, Joseph M.
Abstract : Objective: To identify the frequency of passing return-to-activity tests after anterior cruciate ligament reconstruction (ACLR) and to investigate the influence of patient-specific factors on pass rates. We hypothesized that isolated strength tests would be most difficult to pass and that graft type would be the most influential factor. Design: Cross-sectional. Setting: Laboratory. Participants: Eighty patients with a history of primary, unilateral ACLR, and 80 healthy controls participated. Interventions: Bilateral isokinetic strength, isometric strength, and single-leg hop tests were recorded during a single visit. The International Knee Documentation Committee (IKDC) Subjective Knee Evaluation measured subjective knee function, and the Tegner Activity Scale measured physical activity level. Main Outcome Measures: Pass rates were calculated for 3 thresholds of absolute between-limb asymmetry: 0% to 10%, 11% to 15%, and 16% to 20%. Pass rates were compared by sex (male and female), graft type (patellar and hamstrings), meniscal procedure (yes and no), physical activity level (</≥ median Tegner), and time from surgery (</≥ 6 months). Results: Isokinetic quadriceps strength was consistently most difficult to pass, whereas the 6-meter timed hop and crossover hop tests were easiest. Graft type had the greatest influence on pass rates (isometric quadriceps and hamstring strength, hamstrings-to-quadriceps ratio), followed by time from surgery (6-meter timed hop and crossover hop), physical activity (IKDC), and meniscal procedure (6-meter timed hop). Conclusions: Isokinetic quadriceps strength was the most difficult test to pass, and single-leg hop tests were the easiest. Patient-specific factors including graft type, time from surgery, physical activity level, and meniscal procedure may influence the ability to meet return-to-activity criterion after ACLR.